2015
DOI: 10.1080/07391102.2014.1003146
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of trypsin specificity based on QM/MM molecular dynamics simulation and QM/MM GBSA calculation

Abstract: Hydrogen bonding and polar interactions play a key role in identification of protein-inhibitor binding specificity. Quantum mechanics/molecular mechanics molecular dynamics (QM/MM MD) simulations combined with DFT and semi-empirical Hamiltonian (AM1d, RM1, PM3, and PM6) methods were performed to study the hydrogen bonding and polar interactions of two inhibitors BEN and BEN1 with trypsin. The results show that the accuracy of treating the hydrogen bonding and polar interactions using QM/MM MD simulation of PM6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…[13] Experimental studies could be complemented with the calculations involving ONIOM method treating active site quantum mechanically and the surrounding environment with molecular mechanics. [14][15][16][17][18][19] The enzymatic transformations could be investigated with DFT calculations, and the surrounding residues could be treated with molecular mechanics methods in order to include steric constraints induced by the protein environment and the contribution of the noncovalent interactions around the active sites.…”
Section: F I G U R Ementioning
confidence: 99%
“…[13] Experimental studies could be complemented with the calculations involving ONIOM method treating active site quantum mechanically and the surrounding environment with molecular mechanics. [14][15][16][17][18][19] The enzymatic transformations could be investigated with DFT calculations, and the surrounding residues could be treated with molecular mechanics methods in order to include steric constraints induced by the protein environment and the contribution of the noncovalent interactions around the active sites.…”
Section: F I G U R Ementioning
confidence: 99%
“…The method of QM/MM-GBSA get great success to investigate the interaction of inhibitors binding to targets as reported in everywhere. [25][26][27] Here, the hybrid method of semi-empirical Hamiltonian PM6 and MM-GBSA was chosen to calculate binding free energies between hSETD7 and PFI-2 enantiomers to detect the hidden information behind the stereoselectivity of hSETD7. 200 frames collected from the nal 40 ps of QM/MM MD trajectory with an interval of 200 fs were used for calculating the binding energies.…”
Section: Potential Energy Surfaces Scanningmentioning
confidence: 99%
“…In order to more accurately investigate the hydrogen bond for insight into the stereoselectivity of hSETD7 methyltransferase to the (R/S)-PFI-2, we used the hybrid quantum mechanics/molecular mechanics (QM/MM) MD simulations that had been successfully applied in many researches. [25][26][27] In this study, the QM regions were displayed in Fig. 3, where the average surface of electrostatic potential (EPS) was plotted.…”
Section: Hydrogen Bonds Analysis Based On Qm/mm MD Simulationsmentioning
confidence: 99%
“…Chen et al 264 compared the performance of several semiempirical methods, including RM1, as well as DFT, in the investigation of hydrogen bonds and polar interactions of two inhibitors of the enzyme trypsin. Results showed that PM6 was the best semiempirical method to describe the interactions between the ligands and trypsin.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Results showed that PM6 was the best semiempirical method to describe the interactions between the ligands and trypsin. 264 In addition, the authors predicted Δ bind G (Gibbs energy of binding) of the two ligands on trypsin by using QM/MM GBSA (generalized Born and surface-area solvation) methodology. The results revealed that all computational methods gave similar results for such property.…”
Section: Molecular Dynamicsmentioning
confidence: 99%